A biographical sketch of Johannes Jessenius: 410th anniversary of his Prague dissection - Kachlik, David; Vichnar, David; Musil, Vladimir; Kachlikova, Dana; Szabo, Kristian; Stingl, Josef (Clinical anatomy (New York, N.Y.), 2012)
This article focuses on Johannes Jessenius (Ján Jesenský) (1566-1621), with particular attention paid to his famous Prague dissection and its publication (2011 marking its 410(th) anniversary). Jessenius was a physician, surgeon, anatomist, scholar, philosopher, and university authority. We focus on the life and main contribution of Jessenius based on his 1600 Prague dissection, the Anatomiae, Pragae (1601). Borovanský described Jessenius' book as "not as a textbook, but as a publication aiming at educated laymen with the purpose of advertising, filled with quotations of old classical authors." This work presents an important part of the Central European scientific, cultural, and political life of the late Renaissance period.
Keywords: rukopisy lékařské jako téma; History, 17th Century; Dissection; Česká republika; History, 16th Century; Humans; lidé; disekce; Autopsy; anatomie; pitva; dějiny 16. století; dějiny 17. století; Anatomy; Czech Republic; Manuscripts, Medical as Topic; Books; knihy